Performance of a dual-stage inerter-based vibration isolator - Yang, Jian; Jiang, Jason Z.; Zhu, Xiang; Chen, Hao (Elsevier, 2017)
This paper investigates the dynamic behaviour and performance of a dual-stage inerter-based vibration isolator. Force transmissi-bility and vibration power flow variables are used as performance indices to evaluate the effectiveness of the inerter-based vibration isolator. Vibration power input, transmission and dissipation characteristics of the system are examined. It is found that the inclusion of inerters in dual-stage vibration isolator can reduce force and vibration power flow transmission over a larger band of excitation frequencies. The addition of inerters can also introduce notches in the curves of force transmissibility and time-averaged transmitted power such that the vibration transmission may be greatly suppressed at pre-determined excitation frequencies. These findings demonstrate the potential benefits of employing inerters in vibration isolation and facilitate better understanding of vibration mitigation systems with such element.